PENINGKATAN KOGNITIF DAN MOTIVASI AL-ISLAM MELALUI MODEL COOPERATIF LEARNING MAKE AND MATCH - supri supri (Muhamadiyah, 2018)
This study aims to improve cognitive abilities and motivation of children in Al-Islamic subjects in class V Even Semester SD Muhammadiyah Branjang Yogyakarta. This study is a Classroom Action Research (CAR) using data collection techniques in the form of documentation, observation, and evaluation. Data comes from documentation studies, results of observation, and evaluation. The analysis used is descriptive analysis. The results of the research on the pre-action showed that there was a cognitive improvement and motivation of children in Al-Islam Education during learning as evidenced by the students' conditional data, namely the cognitive abilities of students who reached KKM 3 people or 23.08% or in the category of lacking because they had not used the learning model , while in the improvement of the first cycle students who reach KKM become 9 people or 69.23% or in enough categories because they have used the learning model and in the improvement of the second cycle students who reach KKM there are 12 people or 91.31% or in the good category because of the use Cooperative Learning Make and Match learning model maximally.